Development of Diorama Media to Improve Students' Understanding of Ecosystem Material - Wirda Indah; Annisa Khoirillah; Nur Fadli Fachrial Hazhar; Sofia F Rahmani (Jurnal Ilmiah Pendidikan Lingkungan dan Pembangunan, 2025)
This study aimed to develop a learning media in the form of a diorama specifically designed to improve third grade elementary school students’ understanding of ecosystem material in the Natural and Social Sciences (IPAS) subject. The research approach used Research and Development (R&D) based on the Borg and Gall stages—beginning with needs analysis, planning, product development, trial implementation, followed by revisions and final evaluation.Statistical test results showed that the calculated t-value was 0.0961, whereas the critical t-table value was 0.0948, indicating tₕᵢₜᵤₙg > tₐbₑl (critical). This implies a significant difference in students' understanding before and after using the diorama learning media—in other words, the media is effective in enhancing students’ comprehension of ecosystem material. Moreover, qualitative analysis through teacher observations and student feedback showed that the diorama media increased student motivation, interest, and active participation in learning. The media was also considered engaging and easy to understand by third grade students.The study concludes that the development of acrylic diorama learning media is highly relevant, effective, and dynamic, and is recommended for broad application in teaching ecosystem topics at the elementary school level.